Simion Bărnuțiu – Pioneer in the Development of the Law Sciences and of the Legal Education in Romania - IOVAN, Marțian (Journal of Legal Studies, 2017)
The author analyses in this paper S. Bărnuțiuâ€Ÿs contribution to the establishment of the legal education and to the development of the sciences of the Law in the Romanian area during the mid-19th century. Adept of the natural law philosophy, ardent promotor of human and peopleâ€Ÿs rights, Bărnuțiu remains a personality of reference in the Romaniansâ€Ÿ history not only for being the political leader and ideologist of the Transylvanian 1848 Revolution, but also for establishing the legal education at the University of Iasi by inspiring himself from the curriculum of the profile schools of law from the Western Europe. Having a unitary conception on the law and on the history of law, considering the law from a systemic perspective, Bărnuțiu contributed into the edification of a modern, constitutional, and democratic State in the united Romanian Principalities.